ADVANCING SUSTAINABLE ENVIRONMENTAL STRATEGIES IN THE COTTON INDUSTRY THROUGH DUST EMISSION REDUCTION - Tursunov, Ahror (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents a systematic analysis of dust emissions and their ecological and sanitary impacts in cotton processing plants located in the Namangan region of Uzbekistan. The study evaluates the concentrations of PM2.5 and PM10 particles and compares them with World Health Organization (WHO) guidelines. The findings indicate that dust pollution levels in cotton processing exceed international safety standards by 12–13 times. Comparative analysis with international practices from India, China, and the USA demonstrates that the implementation of advanced filtration technologies can significantly reduce dust emissions. The article concludes with practical recommendations for enhancing industrial hygiene, implementing real-time monitoring systems, and aligning with international environmental standards.